Development of Modules Based on Scientific Approach and Project Based Learning on Economic Subject - Cyndi Eka; Waspodo Tjipto Subroto; Luqman Hakim (PT ARRUS Intelektual Indonesia, 2022)
The purpose of this study is to produce teaching materials in the form of economic modules that are appropriate for learning activities with the feasibility of modules based on expert validation to assess the components of material, language, and graphics, and the effectiveness of the economics module from pretest-posttest and student responses. The model used in this study is a 4D model, namely define, design, develop, and disseminate. The subjects in this study were students of class XI IPS MA Nurul Islam Pungging and the object developed was a module based on a scientific approach and project based learning on economics subjects in SMA/MA class XI in the second semester. The results of the validation of the experts showed that the feasibility of the material component was 92%, the language component was 91%, and the graphic component was 94%. The overall average is 94.7% in the very appropriate category and the student response is 96.66% in the very feasible category, and the effectiveness obtained from the classical completeness of students is 90% with a gain score of 0.76 in the high category. So it can be concluded that the economic module based on a scientific approach and project based learning is feasible to use in economics learning. The suggestion from this research is that it needs to be further developed in accordance with the progress of science and technology with an android-based system or application and the expansion of the material in the module up to one year.